Risk factors and distribution pattern of lateral lymph node recurrence after central neck dissection for cN1a papillary thyroid carcinoma - Binbin Long; Mingxu Luo; Ke Zhou; Tao Zheng; Wenfang Li (BMC Surgery, 2024)
Abstract Background The indication and extent of selective lateral neck dissection (LND) for cN1a papillary thyroid carcinoma (PTC) remain uncertain. The present study aimed to identify potential predictors and distribution pattern of lateral lymph node recurrence (LLNR) after central neck dissection in cN1a PTC patients. Methods The cN1a PTC patients who underwent initial central neck dissection at our centre were retrospectively reviewed, and the median follow-up period was 6.8 years. Reoperation with LND was performed when LLNR was confirmed. Risk factors for LLNR were identified, and the metastatic status of each lateral level was recorded. Results Of the 310 patients enrolled in the present study, fifty-eight patients (18.7%) presented with LLNR. Six independent factors, including tumour diameter, pathological T4 stage, number of involved central lymph nodes, pTNM stage, extrathyroidal extension, and I131 treatment (P values < 0.05) were identified via multivariate analysis. LLNR was found at level II in 26 patients (44.8%), level III in 38 patients (65.5%), level IV in 30 patients (51.7%), and level V in 8 patients (13.8%). The number of positive lateral lymph nodes at levels II, III, IV and V was 44 (22.9%), 76 (39.6%), 63 (32.8%), and 9 (4.9%), respectively. Conclusions For cN1a PTC patients who underwent central neck dissection, tumour diameter ≥ 2 cm, pathological T4 stage, number of involved central lymph nodes ≥ 3, pTNM stage III-IV, extrathyroidal extension, and failure to receive I131 treatment were independent predictors of LLNR, which was more likely to occur at levels III and IV.